2019
DOI: 10.1186/s13014-019-1372-3
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle mass correlates with increased toxicity during neoadjuvant radiochemotherapy in locally advanced esophageal cancer: A SAKK 75/08 substudy

Abstract: Background Sarcopenia, the critical depletion of skeletal muscle mass, is an independent prognostic factor in several tumor entities for treatment-related toxicity and survival. In esophageal cancer, there have been conflicting results regarding the value of sarcopenia as prognostic factor, which may be attributed to the heterogeneous patient populations and the retrospective nature of previous studies. The aim of our study was therefore to determine the impact of sarcopenia on prospectively co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 26 publications
3
21
3
1
Order By: Relevance
“…The results of the QUIPS assessment of all included studies are summarized in Figure 2. Out of the 31 included studies, seven studies had a low risk of bias [6,16,19,24,25,34,38], 16 studies had a moderate risk of bias [5,7,8,[21][22][23]26,[28][29][30][31][32]35,37,43,44], and eight had a high risk of bias [20,27,33,36,[39][40][41][42]. The domains study participation, study confounding, and statistical analysis and reporting were most frequently assessed as having a high risk of bias.…”
Section: Study Quality Assessmentmentioning
confidence: 99%
“…The results of the QUIPS assessment of all included studies are summarized in Figure 2. Out of the 31 included studies, seven studies had a low risk of bias [6,16,19,24,25,34,38], 16 studies had a moderate risk of bias [5,7,8,[21][22][23]26,[28][29][30][31][32]35,37,43,44], and eight had a high risk of bias [20,27,33,36,[39][40][41][42]. The domains study participation, study confounding, and statistical analysis and reporting were most frequently assessed as having a high risk of bias.…”
Section: Study Quality Assessmentmentioning
confidence: 99%
“…However, skeletal muscle mass and strength may furtherly be reduced during NAT (9), because of chemotherapy-related toxicities (10), disease progression (11) and adverse postoperative complications (12). Until now, whether sarcopenia would influence the survival rate of EC patients remains controversial (13,14). Therefore, we aim to assess the effects of sarcopenia on the prognosis of EC patients undergoing NAT in this meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…[18] Also, in stage III TNM esophageal cancer treated with neoadjuvant chemoradiotherapy followed by esophagectomy, the presence of sarcopenia was not associated with negative short-and longterm outcome. [13,50] Conversely, one study showed that patients with gastric cancer who had preoperative sarcopenia and were converted to non-sarcopenic status did not present major postoperative complications. [51] Also, the phenotype of sarcopenia may play a role.…”
Section: Discussionmentioning
confidence: 99%